Paradoxes of power and leadership - Cunha, Miguel Pina e 1965-; Clegg, Stewart 1947-; Rego, Arménio ca. 20.-21. Jh; Berti, Marco 1965- (Routledge, Taylor & Francis Group, 2021)
Leadership and paradox -- Paradoxes of self-leadership -- Paradoxes of dyadic relationships -- Paradoxes of team dynamics -- Paradoxes at the organizational level -- Recurring paradoxes and ten lines of action
Enthält Literaturverzeichnis und Index
Keywords: Führung; Unternehmen; Leadership; Organizational behavior; Executive ability; Management